PERUBAHAN TRADISI PITON-PITON DI NAGARI LIMAU PURUT KABUPATEN PASAMAN BARAT : - Hani Kurnia Wati; Maulid Hariri Gani; Gusneli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The python-piton (mitoni) tradition is a Javanese tradition performed at the seventh month of pregnancy as an expression of gratitude and a prayer for the safety of the mother and unborn child. This tradition is still preserved by Javanese transmigrants in West Pasaman Regency, particularly in Limau Purut Village, Kinali District. This study aims to analyze the process, meaning, and educational values contained within the python-piton tradition. The research method used was qualitative research with a descriptive approach, using data collection techniques such as interviews, observation, documentation, and literature review. The results indicate that the python-piton tradition is carried out through several stages, including the ritual bath (siraman), the changing of seven types of cloth, the splitting of the coconut, and a celebration (selamatan) with the serving of traditional foods such as rujak (rice cake) and dawet (dried fruit). This tradition has undergone several changes in its implementation, but remains preserved by the community as a form of preserving Javanese culture in diaspora areas. Furthermore, the python-piton tradition embodies religious, social, and community values, as well as hopes for the safety of the mother and unborn child. This tradition also reflects the acculturation of Javanese culture with elements of local beliefs and customs.